Mobile Phones Will Not Eliminate Digital and Social Divides: How Variation in Internet Activities Mediates the Relationship Between Type of Internet Access and Local Social Capital in Detroit. (April 2022) - Reisdorf, Bianca C.; Fernandez, Laleah; Hampton, Keith N.; Shin, Inyoung; Dutton, William H.
This study examines the relationship between mode of Internet access, variety of online activities, and the potential for the Internet to contribute to local social capital in distressed, urban communities. Based on a sample of 525 telephone surveys in Detroit, findings show that breadth of access predicts participation in a larger variety of online activities, which is associated with higher levels of local social capital. Neither public Internet access, home broadband, nor Internet access through a mobile phone data plan alone affords participation in a full range of social capital-enhancing activities. The findings highlight the potential problems of initiatives that assume equivalent social outcomes through nonequivalent modes of access, such as providing Internet access through mobile phones in place of home broadband. Efforts to enhance a city's social infrastructure by providing Internet access are best served when individuals have multiple points of access available.